Macrophage migration inhibitory factor derived from spinal cord is involved in activation of macrophages following gecko tail amputation. Issue 12 (5th November 2019) - Wang, Yingjie; Wei, Sumei; Song, Honghua; Zhang, Xuejie; Wang, Wenjuan; Du, Nan; Song, Tiancheng; Liang, Hao; Chen, Xiaojun; Wang, Yongjun
Abstract : Macrophages and their initiation of acute inflammation have been defined to be functionally important in tissue repair and regeneration. In injury‐induced production of macrophage migration inhibitory factor (MIF), which has been described as a pleiotropic protein that participates in multiple cellular and biologic processes, it is unknown whether it is involved in the regulation of macrophage events during the epimorphic regeneration. In the model of gecko tail amputation, the protein levels of gecko MIF (gMIF) have been determined to be significantly increased in the nerve cells of the spinal cord in association with the recruitment of macrophages to the lesion site. gMIF has been shown to interact with the CD74 receptor to promote the migration of macrophages through activation of Ras homolog gene family member A and to trigger inflammatory responses through MAPK signaling pathways. The determination of microsphere phagocytosis also indicated that gMIF could enhance macrophage phagocytosis. gMIF‐mediated recruitment and activation of macrophages have been found to be necessary for gecko tail regeneration, as evidenced by the depletion of macrophages using clodronate liposomes. The results present a novel function of MIF during the epimorphic regeneration, which is beneficial for insights into its pleiotropic property.—Wang, Y., Wei, S., Song, H., Zhang, X., Wang, W., Du, N., Song, T., Liang, H., Chen, X., Wang, Y. Macrophage migration inhibitory factor derived from spinal cord is involved in activation of macrophages following gecko tail amputation. FASEB J. 33, 14798‐14810 (2019). www.fasebj.org